Relevance of Financial Service Advertisements in Investment Decisions and Purchase of Financial Products : Evidence from the Indian Insurance Sector - Javed, Sarfaraz; Husain, Uvesh; Pathak, Namrata (Indian Journal of Marketing, 2021)
This study investigated the impact of investment decision-making on financial product purchases and explored the mediating role of financial services advertisements in India’s insurance sector. Data collected from 447 responses were analyzed using SPSS and AMOS. SEM was conducted to testify the hypotheses. The results identified that the entertainment variable played a vital role in determining financial product purchases and investment decision-making. The results also indicated that financial services advertising, perceived reality, and usefulness positively and significantly mediated between financial product purchases and investment decision making. The study provided valuable clues for the investment and selection of financial products. The insights acquired from this study may have significant consequences for corporate promotional behavior, investor relations systems, and coordinated public engagement activities.